(untitled) (Oxfor, 1998)
The Student's Solutions Manual for Physical Chemistry, Sixth Edition is very helpful and provides enough information in their problem solving to understand the basis of the chapters and the problems.
Keywords: Chemistry, physical and theoretical; Problems, exercises, etc